2013
DOI: 10.1080/17461391.2012.756542
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of performance development in elite athletes

Abstract: This investigation sought to contrast generalised models of athlete development with the specific pathway trajectories and transitions experienced by 256 elite athletes across 27 different sports. All participants completed the National Athlete Development Survey and within it, the Athlete Development Triangle featuring the differentiation of junior and senior competition experience and progression. Developmental initiation; prevalence, magnitude and direction of pathway trajectory; extent of concurrent junior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
119
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(136 citation statements)
references
References 33 publications
9
119
0
8
Order By: Relevance
“…As 63% of the players in the present study reported to have participated in sports outside football and 37% only have participated in football, both pathways of the DMSP seem to be present within this elite group. However, such a dichotomous model does not necessarily reflect the athletes' individual variations in development or the underlying variables that could affect this development, because it is "likely that these variables can combine into a number of developmental pathways" (Ford & Williams, 2012, p. 349;Gulbin, Weissensteiner, Oldenziel, & Gagné, 2013). Such variables could include sports' similarities (Baker et al, 2003), number of hours spent in different activities , variation in the content of different activities (Ford et al, 2009) or the level at which an athlete practices and competes (Gulbin et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…As 63% of the players in the present study reported to have participated in sports outside football and 37% only have participated in football, both pathways of the DMSP seem to be present within this elite group. However, such a dichotomous model does not necessarily reflect the athletes' individual variations in development or the underlying variables that could affect this development, because it is "likely that these variables can combine into a number of developmental pathways" (Ford & Williams, 2012, p. 349;Gulbin, Weissensteiner, Oldenziel, & Gagné, 2013). Such variables could include sports' similarities (Baker et al, 2003), number of hours spent in different activities , variation in the content of different activities (Ford et al, 2009) or the level at which an athlete practices and competes (Gulbin et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…However, such a dichotomous model does not necessarily reflect the athletes' individual variations in development or the underlying variables that could affect this development, because it is "likely that these variables can combine into a number of developmental pathways" (Ford & Williams, 2012, p. 349;Gulbin, Weissensteiner, Oldenziel, & Gagné, 2013). Such variables could include sports' similarities (Baker et al, 2003), number of hours spent in different activities , variation in the content of different activities (Ford et al, 2009) or the level at which an athlete practices and competes (Gulbin et al, 2013). Through earlier studies on elite youth football players, for instance, the early engagement hypothesis emerged as an alternative pathway to the two originally included in the DMSP, to cover the large amount of time such players have spent in footballspecific play rather than multiple sports or deliberate practice (e.g., Ford et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…There was potential for the results from this study to show that competition periods could have a negative effect on physical development; however, the net gains of the training period still show substantial improvement. Gaining competition exposure for developing athletes is a key element of any high-performance sport's programme (20), it is important to consider a holistic approach to training where the inclusion of competition may have a positive effect on other elements of on-court performance, even if physical performance was temporarily affected. The net gain in sports performance is an important element for strength and conditioning professionals and sports coaches to consider when planning and administering any programme.…”
Section: Discussionmentioning
confidence: 99%
“…While the pyramid model has popular appeal, there has been no empirical testing that confirms its veracity. While the notion of sequential progression through the pyramid seems logical, it does not reflect reality (Green, 2005;Gulbin, Weissensteiner, Oldenziel, & Gagné, 2013), nor does it offer guidance for organisations in facilitating movement through the pyramid (Sotiriadou, Shilbury, & Quick, 2008).…”
Section: Introductionmentioning
confidence: 95%